2016
DOI: 10.2174/1570159x13666150727220944
|View full text |Cite
|
Sign up to set email alerts
|

Kappa Opioids, Salvinorin A and Major Depressive Disorder

Abstract: Opioids are traditionally associated with pain, analgesia and drug abuse. It is now clear, however, that the opioids are central players in mood. The implications for mood disorders, particularly clinical depression, suggest a paradigm shift from the monoamine neurotransmitters to the opioids either alone or in interaction with monoamine neurons. We have a special interest in dynorphin, the last of the major endogenous opioids to be isolated and identified. Dynorphin is derived from the Greek word for power, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 119 publications
(191 reference statements)
0
25
0
Order By: Relevance
“…Thus our data do not distinguish between the respective roles mu opioid receptor and kappa opioid receptor in mediating ketamine’s antidepressant effects. Nonetheless, given the available data implicating mu opioid receptor-based mechanisms of antidepressant efficacy, inconsistent findings regarding kappa opioid receptor antagonists in depression (57, 58), and ketamine’s putative kappa agonist mechanism (21, 59), we favor the interpretation that ketamine produces its acute antidepressant response primarily through direct and/or indirect actions at the mu opioid receptors. Naltrexone when chronically administered alone in normal healthy controls as well as individuals with mood and substance disorders has been demonstrated to either act as an antidepressant or be moodneutral across several placebo-controlled trials (23, 3338), suggesting that naltrexone is not simply acting as a depressionogenic agent in this case, but rather providing selective blockade of the antidepressant effects produced by ketamine.…”
Section: Discussionmentioning
confidence: 90%
“…Thus our data do not distinguish between the respective roles mu opioid receptor and kappa opioid receptor in mediating ketamine’s antidepressant effects. Nonetheless, given the available data implicating mu opioid receptor-based mechanisms of antidepressant efficacy, inconsistent findings regarding kappa opioid receptor antagonists in depression (57, 58), and ketamine’s putative kappa agonist mechanism (21, 59), we favor the interpretation that ketamine produces its acute antidepressant response primarily through direct and/or indirect actions at the mu opioid receptors. Naltrexone when chronically administered alone in normal healthy controls as well as individuals with mood and substance disorders has been demonstrated to either act as an antidepressant or be moodneutral across several placebo-controlled trials (23, 3338), suggesting that naltrexone is not simply acting as a depressionogenic agent in this case, but rather providing selective blockade of the antidepressant effects produced by ketamine.…”
Section: Discussionmentioning
confidence: 90%
“…While κ receptor agonists frequently precipitate dysphoric mood changes in humans and depression‐like symptoms in experimental animals (Ranganathan et al , ), several κ receptor antagonists were found to exert anti‐depressant effects (Lutz and Kieffer, ) (Table ). A combined pharmacological profile of a μ receptor agonist and κ receptor antagonist could thus not only produce analgesia but also treat depressive symptoms, a frequent comorbidity in chronic pain patients (Taylor and Manzella, ). The compound best studied in this context is buprenorphine, which is a partial μ receptor agonist with a weak κ receptor antagonistic profile.…”
Section: Rationale For the Development Of Multi‐targeting Opioid Ligandsmentioning
confidence: 99%
“…It has been hypothesized that activation of KOR receptor by dynorphin leads to a reduction in dopamine release, thus producing anhedonia and depressive symptoms. Accordingly, KOR antagonists exert relevant antidepressant effects in animal models of depression (Taylor and Manzella, 2016).…”
Section: B Pharmacological Strategies In Treatmentresistant Depressionmentioning
confidence: 99%